1987
DOI: 10.1055/s-2008-1052486
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Intracranial Aneurysms in Childhood:A Case Report and Review of the Literature

Abstract: This report describes three individuals belonging to one family, who were affected with ruptured intracranial aneurysms (IAs) at a rather young age, 4, 15 and 23 years respectively. Familial IAs at this young age have not been described before. The evidence for a developmental, eventually inherited origin of familial IA in childhood is discussed with reference to the low occurrence of non-familial IA in childhood, IA-features in non-familial cases (localisation, multiplicity, size) and the association with (ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…[311][312][313][314][315] Although individuals with a familial aneurysm remain asymptomatic until adulthood, 316 -319 2 children in 1 family developed SAH from a ruptured aneurysm. 320 Siblings of individuals with an intracranial aneurysm have more risk of developing an aneurysm than other family members. 321 One study found a 4-fold increase in the prevalence of intracranial aneurysms among first-degree relatives of aneurysm patients, but many of these individuals remained asymptomatic at the time of publication, and most of the individuals were adults, not children.…”
Section: Disorders Associated With Intracranial Aneurysmmentioning
confidence: 99%
“…[311][312][313][314][315] Although individuals with a familial aneurysm remain asymptomatic until adulthood, 316 -319 2 children in 1 family developed SAH from a ruptured aneurysm. 320 Siblings of individuals with an intracranial aneurysm have more risk of developing an aneurysm than other family members. 321 One study found a 4-fold increase in the prevalence of intracranial aneurysms among first-degree relatives of aneurysm patients, but many of these individuals remained asymptomatic at the time of publication, and most of the individuals were adults, not children.…”
Section: Disorders Associated With Intracranial Aneurysmmentioning
confidence: 99%
“…Multiple ICA aneurysms are a well known feature of autosomal polcystic kidney disease [27]. An unusually high incidence of multiple aneurysms has been reported in children affected with HIV infection, immune deficiencies, moyamoya disease and familial inheritance [28,29,30,31,32,33,34]. In familial cases, the correlation between the locations of aneurysms in relatives indicates a genetic role in aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In familial cases, the correlation between the locations of aneurysms in relatives indicates a genetic role in aneurysm formation. Screening of high-risk children with familial SAH can be done using MR angiography or a CT angiogram [32, 34]. A deficiency of type III collagen causing fragmentation of the internal elastic lamina is also postulated [34].…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs auteurs présentent l'étude d'une seule famille en y exposant les cas (Ullrich et Sugar 1960;Graf 1966;Beumont 1968;Kak 1970;Brisman et Abbassioun 1971;Edelsohn et al 1972;Nagae et al 1972;Hashimoto 1977;Acosta-Rua 1978;Fox et Ko 1980;Fox 1982;Halal et al 1983;Berg et al 1987). Toutes ces études nous amènent à nous interroger de plus en plus sur les facteurs qui prédisposent ces individus à développer un anévrisme.…”
Section: éPidémiologie Génétiqueunclassified